Technology, Governance, and Workforce Management in Hospitals: A Scoping Review of Human Resource Management Evidence - Oktaviyanti, Herlina; Aini, Qurratul (Journal of Applied Nursing and Health, 2026)
Background: Evidence on hospital human resource management (HRM) remains fragmented, particularly regarding technology integration, public–private differences, and the management of non-clinical staff. This scoping review mapped the available evidence to identify key themes and research gaps in these areas. Methods: This scoping review was guided by the Arksey and O’Malley framework and reported in line with PRISMA-ScR. The review used the PCC framework (Population: hospital HRM stakeholders; Concept: technology integration, public-private HRM differences, and non-clinical workforce management; Context: hospitals and healthcare facilities). Searches were conducted in PubMed, Scopus, and Web of Science for English-language empirical studies published from 2020 to 2025. Eligible studies were qualitative, quantitative, or mixed-methods; non-empirical articles, non-English publications, studies before 2020, and studies outside healthcare-facility settings were excluded. After screening 487 records, removing 75 duplicates, assessing 57 full texts, and excluding 42 reports, 15 studies were included. Data were charted by author, year, country, design, focus, and key findings, then synthesized thematically. Results: Five themes emerged from thematic synthesis: HRM as a strategic capability; technology-enabled HRM; motivation and retention of non-clinical staff; public-private differences in HRM practices; and the relationship between HRM, service quality, and patient satisfaction. The evidence suggested that digital tools can improve monitoring, coordination, and decision-making, but implementation depends on organizational readiness and available resources. Public hospitals were generally constrained by bureaucracy and limited flexibility, whereas private hospitals were more adaptable. Research on non-clinical staff remained limited, especially regarding career pathways, retention strategies, and unit-level HR practices. Conclusion: Hospital HRM is shifting from an administrative function to a strategic, technology-supported system that influences service quality and organizational performance. This review contributes a consolidated map of evidence on digital HRM integration, public-private differences, and non-clinical workforce management, while showing that these areas remain underexplored. Future studies should prioritize comparative designs, stronger theoretical.